2019
DOI: 10.1002/fsn3.1076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccharomyces cerevisiae in association with Torulaspora delbrueckii on the aroma and amino acids in longan wines

Abstract: This study investigated the effects of monocultures of Saccharomyces cerevisiae and Torulaspora delbrueckii as well as simultaneous and sequential cultures of S. cerevisiae and T. delbrueckii on the nonvolatile and volatile compounds in longan wines. The four cultures had similar characteristics in longan wines. The main amino acids in all the fermentations were glutamic acid, arginine, alanine, leucine, proline, and GABA. The main volatile compounds in longan wines were ethanol, isoamyl alcohol, isobutanol, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…As suggested by the literature, a conjugation of S. cerevisiae and T. delbrueckii may be an option for improving wine quality by combining the advantages of both species [ 5 , 30 , 31 , 32 , 33 ]. Using protoplast fusion, Santos et al [ 25 ] produced a hybrid strain (F1-11) of both species.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by the literature, a conjugation of S. cerevisiae and T. delbrueckii may be an option for improving wine quality by combining the advantages of both species [ 5 , 30 , 31 , 32 , 33 ]. Using protoplast fusion, Santos et al [ 25 ] produced a hybrid strain (F1-11) of both species.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi molds and yeasts are used as main starter in rice wine, which are responsible for starch degradation and alcohol fermentation, respectively (Sanoppa, Huang, & Wu, 2019; Yang et al., 2017). Meanwhile, wine industrial fermentation tends to use S. cerevisiae to ensure the smooth progress of wine fermentation, but that reduces the flavor diversity of wine to some extent (Krogerus, Magalhães, Vidgren, & Gibson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They performed co-inoculation using active dry wine yeasts and aroma-producing yeast in the ratio of 1:1 to analyze the influence of different fermentation parameters (sugar content, acidity, fermentation temperature, and fermentation time) on basic physicochemical indexes and sensory characteristics of longan wine. Sanoppa et al (2019) probed the effects of inoculation of Torulaspora delbrueckii on the nonvolatile and volatile compounds in longan wines. They found that longan wine fermented with T. delbrueckii by co-inoculation produced the highest number of total volatile aromatic compounds.…”
Section: Preparation Of Fermented Longan Winementioning
confidence: 99%